Theoretical Model of Intelligence Integration to Improve Self-Directed Learning in Mathematics in the 21st Century - Ainul Marhamah Hasibuan; Syahrina Anisa Pulungan; Ramadhani Ramadhani (MASI Mandiri Edukasi, 2026)
This study examines the effectiveness of the Theoretical Model of Intelligence Integration in improving students’ self-directed learning in 21st-century mathematics education. The research addresses the problem that many students remain dependent on teacher guidance and have limited ability to regulate their own learning processes. Therefore, this study aims to evaluate whether integrating intellectual, emotional, and spiritual intelligence can strengthen students’ self-directed learning in mathematics. A quantitative approach using a true experimental posttest-only control group design was applied, involving 120 eighth-grade students divided equally into experimental and control groups through cluster random sampling. The experimental group received instruction based on the integration of multiple intelligences through stages of contextual problem orientation, self-awareness reflection, strategic problem solving, collaborative discussion, and reflective evaluation, while the control group received conventional instruction. Data were collected using a validated self-directed learning questionnaire measuring awareness, learning strategies, learning activities, evaluation, and interpersonal skills. Hypothesis testing used descriptive statistics, regression, and correlation analysis. The results show a substantial difference between groups and a strong regression effect (R² = 0.823), indicating that the model significantly improves students’ learning autonomy and provides a holistic framework for strengthening self-regulation in mathematics learning.